Determination of Trace Amounts of Cobalt by Flame Atomic Absorption Spectrometry after Solid-Liquid Extraction and Preconcentration with Use of Nitroso-R Salt - Ali Taher, Mohammad (Asian Journal of Chemistry, 2010)
Cobalt was quantitatively retained by disodium 1-nittoso-2- naphthol-3,6-disulfonate (nitroso-R salt) and tetradecyldimethylbenzylammonium chloride on microcrystalline naphthalene in the pH range 3.6-8.2 from large volumes of aqueous Solutions of various alloys and biological samples. After filtration, a solid mass consisting of the cobalt complex and naphthalene was dissolved with 5 mL of dimethylformamide and the metal was determined by flame atomic absorption spectrometry (FAAS). The cobalt complex could alternatively be quantitatively adsorbed on tetradecyldimethylbenzylammonium- naphthalene adsorbent packed in a column and determined similarly. In this case, 0.50 μg of cobalt can be concentrated in a column from 500 mL of aqueous sample, where its concentration is as low as 1.0 ppb. Eight repliate determinations of 1.0 ppm of cobalt gave a mean absorbance of 0.050 with a relative standard deviation of 1.9%. The sensitivity for 1% absorption was 88 ppb. Various parameters, such as the effect of the pH, the volume of the aqueous phase and the interference of a number of metal ions on the determination of cobalt, have been studied in detail to optimize the conditions for the determination of cobalt in various alloys and biological samples.